Strengthening of the phytosanitary and zoosanitary regulation and control agency (AGROCALIDAD) and its national food safety system, based on the experience and management model of the chilean food safety and quality agency (ACHIPIA). Capacity building in AGROCALIDAD to bolster Ecuador’s food safety and quality system - Centro de Gestión del Conocimiento y Cooperación Horizontal (CGCCH) (IICA, 2021)
5 pages